Women climate scientists are connected, productive, and successful but have shorter careers - Chris C. Martin; Andrew Lockley; Steve Hendricks; Cory J. Clark; Ishita Mundra; Nils Matzner (Proceedings of the National Academy of Sciences, 2025)
Scholars have long been concerned about gender representation in scientific research but there has been little work on gender differences in participation and performance in climate science, a field that engages with both male-majority disciplines (e.g., geosciences, engineering) and female-majority disciplines (e.g., life sciences, medical science). This has implications for both gender equity and viewpoint representation. Sampling over 400,000 publications and a similar number of authors, we examine gender differences in several scholarly outcomes including publication count, career survival, coauthor gender, journal status, and mean citation count. We find men and women are similarly productive, successful, and connected, though women have shorter research careers and thus fewer papers. We also find gender homophily effects in collaboration, but no evidence of gender bias in peer review.